126. а)5 * (3+21) = 5 * 3 + 5 * 21 = -5 * (-3 - 21)5 * (-3+21) = -5 * 3 + 5 * 21 = -5 * (3 - 21)5 * (-3-21) = -5 * 3 - 5 * 21 = -5 * (3+21)б)-2 * (5+40) = -2 * 5 - 2 * 40 = 2 * (-5-40)-2 * (5-40) = -2 * 5 + 2 * 40 = 2 * (-5+40)-2 * (-5+40) = 2 * 5 - 2 * 40 = 2 * (5 - 40)-2 * (-5-40) = 2 * 5 + 2 * 40 = 2 * (5+ 40)128.25 + 38 * (59-96) = 25 + 38 * 59 - 38 * 96 = 25 - 38 * (-59+96)25 + 38 * (-59+96) = 25 - 38 * 59 + 38 * 96 = 25 - 38 * (59-96) 25 + 38 * (-59-96) = 25 - 38 * 59 - 38 * 96 = 25 - 38 * (59+96)